Innovative Territorial Clusters - Mindlin, Yurii B.; Novikov, Sergey V.; Kireev, Sergey V.; Adamenko, Alexsandr A.; Belitskaya, Oksana V. (International Journal of Economics and Financial Issues, 2016)
The emergence of new centers of economic growth, which will unite scientific, educational and industrial potentials, and would also enhance the competitiveness of enterprises and the region organizations as research and education in the future will have a multiplier effect on the shaping of economic processes, which helps to attract investment. This trend of building new centers, implementing efficient activities will affect the transition of Russian economy to innovative type of development. The relevance of the implementation of innovative type of economy development on the basis of innovative territorial clusters is dictated by the need to ensure balanced and sustainable development of national economic systems through the unwinding of selected innovative areas of the state. Such territories are actively formed at the present time can become innovative territorial clusters. These formations of the modern world, they had a different policy and the implementation of its activities, to present the latest shapes and signs of competitiveness are a kind of “springboard” in the economy of the future. The competitiveness of the economy of the region, the state, the region now depends not only on technical achievements, inventions, but also on organizational changes that contribute to their business results and marketing innovation in the field of promotion and implementation of regional clusters. Keywords: cluster, innovation, region, competitiveness, cluster policy, efficiency JEL Classifications: F63, O10, O22, O29, L59